Social Media Management - Looy, Amy Van (Springer, 2016)
This book is written as an international handbook and primarily targets students in economics and business administration. Also other students interested in the organization’s way of working or social media management in general are encouraged to read the book. Additionally, business people (ranging from employees to managers and CxOs) who wish to get acquainted with the diverse business aspects of social media will profit from the book.
Technologies and Strategies for Creating Business Value